Police Discretion Policy In Handling Middle/Minor Crimes (Tipiring) Based On Justice Value - Saptanti Lastari; Sri Kusriyah (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to analyze the police discretionary policy in handling minor crimes (Tipiring) not based on the value of justice, analyze the constraints of the police discretionary policy in handling minor crimes (Tipiring) at this time and analyze the police discretionary policy in handling criminal acts (Tipiring) in the future. This study uses a sociological juridical approach, with analytical descriptive research methods. The data used are primary and secondary data which will be analyzed qualitatively. The research problem was analyzed using the theory of justice and the theory of the operation of law. The results of the study conclude that discretion is a police action that must be accounted for based on applicable laws and norms, police discretion is very vulnerable to irregularities and abuse so it needs to be given limits and supervision, so it can be said that it is not fair. Constraints on police discretionary policy in handling minor crimes consist of internal constraints and external constraints on the part of the police. The ideal policy of the Police's discretion in handling minor crimes (Tipiring) is: a) Not against a rule of law. b) In line with legal obligations that require an official action to be taken. c) The action must be appropriate and reasonable and included in the environment of his office, on appropriate considerations based on compelling circumstances, respecting human rights